Composite correction of a unilateral cleft lip nose deformity and alveolar bone grafting - Mokal Nitin; Prabhash; Kale Chintamani (Indian Journal of Plastic Surgery)
Background: Managing the cleft lip nasal deformity has always been a challenge. Even now, there is no single established universally accepted method of correction. The open alveolar gap and the ipsilateral hypoplastic maxilla are two major problems in achieving consistently good results in a cleft lip nasal deformity. In our study, after first assuring the orthodontic realignment of maxillary arches, we combined bone grafting in the alveolar gap and along the pyriform margin, with a formal open rhinoplasty approach. Methods: All the patients underwent orthodontic treatment for preparation of the alveolar bone grafting. During the process of alveolar bone graft, a strip of septal cartilage graft was harvested from the lower border of the septum which also helps to correct the septal deviation. The cancellous bone graft harvested from the iliac crest was used to fill the alveolar gap and placed along the pyriform margin to gain symmetry. Through open rhinoplasty along the alar rim and additionally using Potter′s incision extending to the lateral vestibule, the lateral crura of the alar cartilage on the cleft side was released from its lateral attachment and advanced medially as a chondromucosal flap in a V-Y fashion, in order to bring the cleft-side alar cartilage into a normal symmetric position. The harvested septal cartilage graft was used as a columellar strut. The cleft nostril sill was narrowed by a Y-V advancement at the alar base and any overhanging alar rim skin was carefully excised to achieve symmetry. Results: The results of this composite approach were encouraging in our series of 15 patients with no additional morbidity and a better symmetry of the nose and airway especially in the adolescent age group. Conclusion: This concept of simultaneous approach when appropriate for nasal correction at the time of alveolar bone grafting showed an encouraging aesthetic and functional outcome.